Can melatonin correct the negative effect of experimental diabetes created during the maternal period on fetal rat development and puppies cognitive functions? (Annals of Medical Research, 2021)
Aim: Chronic hyperglycemia can cause cognitive impairments such as learning and memory impairment. In our study, we aimed to investigate the levels of glial fibrillary acidic protein (GFAP), neural cell adhesion molecules (NCAM), lipid peroxidation (LPO), and glutathione (GSH) molecules and the protective effect of melatonin in the brain tissue of baby rats with diabetic mothers.Materials and Methods: Wistar-Albino rats used in the experiments were obtained from Firat University Experimental Research Center. Morris Water Maze Test is a learning and memory test commonly used in rats and mice. In the statistical analysis of the data; one-way analysis of variance (One-way ANOVA) was used to evaluate the significance of NCAM, GFAP, LPO, GSH levels between three groups, and repeated measures analysis of variance (Repeated measures one-way ANOVA) was used to evaluate the Morris Water Maze learning test.Results: Learning was worse in rats whose mothers were diabetic compared to diabetes + melatonin and control groups. With the administration of melatonin to diabetic mothers during their pregnancy, an improvement was observed in the learning ability of baby rats. NCAM 180, GFAP, GSH levels were significantly lower (p